VD_FINDINFO HC / 2020 / 331 vom 20. Mai 2020 - VD Tribunal cantonal (2020)
DÉBITEUR, DIRECTIVEINJONCTION, OBLIGATION D'ENTRETIEN, ENFANT, MAJORITÉ{ÂGE}, FORMATIONEN GÉNÉRAL, DURÉE | 291 CC, 248 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 312 al. 1 CPC (CH)